(untitled) (FAVE Sección Ciencias Veterinarias, 2014)
The aim of this study was to evaluate the activity of cephalexin and the intrinsic antibacterial activity of dog serum and urine on six strains of Escherichia coli, using a dynamic one step dilution in vitro one compartmental model, simulating cephalexin concentrations in these biological fluids during its elimination phase after the intravenous administration. The minimum inhibitory concentration of cephalexin for all strains was 16 µg/mL at standard pH value of 7.4 and at values of 6.5 and 5.5. The CIM was not modified by serum or urine. In the dynamic in vitro model, the efficacy of cephalexin in standard culture medium was 57.2 ± 3.95%, while in presence of serum this increased to 74.3 ± 8.59%, although at higher concentrations than those present in serum, the efficacy of cephalexin in urine was 68.7 ± 4.19%. In conclusion, our study emphasizes the important role of the antibacterial activity of these biological fluids in the success of the antibiotic therapy and proposes the concept of total or global bactericidal effect.